Synthesis and spectroscopic properties of Er3+/Yb3+-codoped GdNbO4 phosphor for thermometry and marine safety protection. (October 2022) - Liu, Mei-Hong; Li, Teng-Teng; Zhang, De-Long
Highlights: Er 3+ /Yb 3+ :GdNbO4 micron-sized phosphor was synthesized by solid-state method. Er 3+ and Yb 3+ concentrations have apparent effects on grain morphology. The phosphor shows strong UCL, good thermal stability and adequate sensitivity. The phosphor shows good chemical stability in high salinity environment. The phosphor is promising for both thermometry and maritime protection. Abstract: Micron-sized GdNbO4 :Er 3+ /Yb 3+ phosphors were prepared by employing a high-temperature solid-state reaction. The crystalline phase, morphology, composition, spectroscopic properties, and impact of rare-earth ion concentration, temperature and high salinity environment were systematically characterized. The extracted results show that phosphor is dominated by the existence of the GdNbO4 crystalline phase. Their morphology and agglomeration phenomenon are strongly dependent on the rare-earth concentration. The phosphor exhibits also excellent up-conversion luminescence (UCL) properties under 980 nm excitation, while a two-photon process accounts for UCL. The following optimal concentrations were selected for enhanced UCL intensity: 10 mol% for Yb 3+ and 3 mol% for Er 3+ . The phosphor shows excellent thermometric performances including strong UCL, good thermal stability, appropriate sensitivity and a wide sensitivity response range. To evaluate the accuracy of the present optical thermometer, the temperature of a heated bench has been comparatively measured by using the proposed optical thermometer and a commercial thermocouple with an accuracy of 1 K. By comparing the temperature values measured by the two methods, it can be concluded that the present optical thermometer has an accuracy better than 1.6 K. In addition, the phosphor exhibits good chemical stability in high salinity environment. Interestingly, its crystalline phase, structure, and UCL spectral structure, intensity and color are all preserved after one-month immersion into a high salinity solution. Graphical abstract: Image, graphical abstract GdNbO4 :Er 3+ /Yb 3+ phosphor was prepared by high-temperature solid-state method. Crystalline phase, morphology, composition, spectroscopic properties, and effects of rare-earth concentration, temperature and high salinity environment were fully characterized. The results show that the phosphor is promising for dual-application in thermometry and safety marks for maritime protection.